Entrepreneurial tendencies of students studying entrepreneurship : the case of Capricorn Tvet College, Limpopo Province - Mathosa, Moji Dorothy (My University, 2018)
Entrepreneurship has become an important issue both locally and internationally in recent years due to its contribution to job creation and economic development. The decision to be entrepreneurial is determined by certain factors, as well as individual traits, and it is a planned behaviour that is not engaged in accidentally. Thus, underlying factors that enhance students’ intention towards entrepreneurship as a career option are vital. However, it is not known if the students have the knowledge of the various support measures available to assist them in starting their own businesses and to support existing ventures. This study wanted to find out if students studying entrepreneurship have any intention of starting their own business ventures and whether they have any knowledge of the support programmes at their disposal. Students studying entrepreneurship as one of their modules at the National Certificate Vocational (NCV) level at Capricorn College for TVET constituted the targeted population for the study. Self-administered questionnaires were given to a total of 170 participants and all of them responded. The results mainly indicated that the students do have the intention of starting their own businesses after completion of their course and that their knowledge of the different entrepreneurship support incentives is not adequate. The study recommends that a more concerted effort be made to make students more aware of engaging in entrepreneurial ventures as a career option and making them aware of the support options that are available to them should they need to start their own businesses. In addition, these support initiatives should publicise their services more, especially to the rural communities.
Thesis (MBA.) -- University of Limpopo, 2018
Keywords: Entrepreneurship; Economic development; Students' tendencies; Entrepreneurship - South Africa,Limpopo.